Adenosine diphosphate-ribosylation greatly affects proteins function: a focus on neurodegenerative diseases - Huang, Chaowen; Xiao, Huilin; Yang, Yang; Luo, Jiankun; Lai, Yixi; Liu, Shizhen; Mao, Kanmin; Chen, Jialong; Wang, Liling (Frontiers in Aging Neuroscience, 2025)
Adenosine diphosphate-ribosylation (ADPRylation) is a reversible posttranslational modification that plays a crucial role in cellular homeostasis and disease development. ADPRylation is produced via nicotinamide adenine dinucleotide hydrolysis and modifies proteins via corresponding transferases, mainly poly(ADP-ribose) polymerases (PARPs), the inhibitors of which have been used in the clinical treatment of cancer. ADPRylation is involved in various physiological processes, including pathogen infection, inflammation, DNA repair, and neurological disorders. In neurodegenerative diseases (NDs), dysregulated ADPRylation contributes to protein aggregation, neuroinflammation, and metabolic disturbances, while targeted modulation shows therapeutic potential. ADPRylation differentially regulates neurodegenerative processes, and PARP inhibitors can reduce neuroinflammation, oxidative stress, and metabolic dysfunction. However, challenges such as poor blood–brain barrier penetration and cell type-specific responses limit clinical translation. This review summarizes recent findings on the role of ADPRylation and PARPs in NDs, highlighting their involvement in protein aggregation and cellular signaling. It emphasizes the importance of ADPRylation in neuronal cells and supports the development of precision therapies targeting this pathway to address current treatment challenges in NDs.